Formulation of Liquid Soap Preparation of Sunflower Seed Oil and KOH with Sweet Orange Scent (Citrus sinensi (L.) Osbeck) - Erin Efrilia; Irda Rizky Wiharti (International Journal Of Health Science, 2025)
This research focuses on the formulation and evaluation of liquid soap using sunflower seed oil and potassium hydroxide (KOH) with a sweet orange aroma. The study aims to determine the optimal ratio of KOH to sunflower seed oil and evaluate the physical properties of the resulting liquid soap, such as organoleptic characteristics, pH, specific gravity, viscosity, foam height, and foam stability. The saponification process was conducted using the hot process method. Three different KOH concentrations (25%, 30%, and 35%) were tested. The results showed that all formulas met the Indonesian National Standard (SNI) for specific gravity, viscosity, and foam height. Formula II (30% KOH) was identified as the best formula due to its highest foam stability (90.67%) and acceptable pH (8), which falls within the recommended range (8–11). These findings indicate that sunflower oil-based liquid soap can be effectively formulated with desired physical properties and potential skincare benefits.